Metastases in pelvic boneswith large soft tissue component in a patient with poorlydifferentiated follicular thyroid cancer - M. U. Radzhapova; I. A. Gulidov; K. B. Gordon; V. V. Polkin; T. A. Agababyan (Сибирский онкологический журнал, 2016)
A clinical case of metastatic diseases of pelvic bones with a large soft tissue component in a patient with poorly differentiated follicular thyroid cancer was presented. Partial tumor regression and pain relief were achieved after chemotherapy.